PENERAPAN GUGUS KENDALI MUTU (GKM) UNTUK MENINGKATKAN HASIL BELAJAR SISWA SMP NEGERI 3 HANAU TAHUN 2013 - Basuki, Agung (Jurnal Aplikasi Manajemen Pendidikan, 2014)
Along with the increasing volume and complexity in the field of education as well as the demand for improving the quality of education. Efforts to improve student mastery of learning outcomes also include efforts to improve the quality of education. Various models and strategies for improving learning outcomes have been widely tested. Which in this study using Quality Circles (QCC). GKM system with seven and seven-step tools as one of the spearheads in Total Quality Management has been widely recognized reliability to improve the quality of the organization.On the application of SMP Negeri 3 Hanau GKM in recommend some causes of low student mastery of learning outcomes. In the first cycle GKM provides recommendations to supplement teaching materials such as student handbooks for 4 subjects, namely: Mathematics, Science, English and Indonesian and improve the students' attention. To motivate teachers to improve students' attention on learning activities conducted classroom observations by peers. Results of the first cycle of activities is entirely mastery of learning outcomes in the first cycle by 58%. And the test results thit to learn science and social studies subjects gave insignificant results. Seeing this condition then conducted follow-up on the second cycle of activities that provide recommendations to further enhance student interest in learning activities, encourage parents to pay attention to student learning outcomes, improve teaching methods and instructional materials complement the IPS. Results of the second cycle activity is mastery of learning outcomes entirely on the second cycle of 86%. At thit test for learning outcomes subjects in English and social studies did not provide significant results. For the pre-test learning outcomes thit cycle with the second cycle all subjects all showed a significant increase in learning outcomes.